MEASURING THE URGENCY OF PANCASILA STUDENT (PELAJAR PANCASILA) PROFILES: PROSPECTIVE PRIMARY EDUCATION TEACHERS’ PERPECTIVES - Serlina Boru Sinaga (Program Studi PGSD Universitas Flores, 2022)
Pancasila Student profiles launched by the government through the Ministry of Education, Culture, Research, and Technology were aimed at formulating the main goal of national education in disruptive era. The objective of this research was to describe the perspective of primary teacher education students on Pancasila Student Profiles. The research design used was descriptive research design with qualitative method. The study was conducted in a state university in Papua as the barometer of education quality in rural and border area. There were 50 students investigated and most of them are in the first year college. Questionnaire, interview, observation and documentation were used as the technique of data collection. The data were analyzed by employing data analysis techniques; data reduction, data display, and drawing conclusion. The results showed that Pancasila Student profiles are important for prospective teachers of primary education. However, most students have no knowledge and understanding about the profiles. All education policy making and practitioners must work together by hand-in-hand to socialize the profiles either at schools or at university.